2022
DOI: 10.1007/s13300-021-01191-y
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of Heart Failure and Chronic Kidney Disease are Associated with Increased Mortality Risk in Early Stages of Type 2 Diabetes Mellitus: Analysis of a Japanese Real-World Hospital Claims Database

Abstract: Introduction: To assess the initial manifestation of comorbidities and their impact on mortality risk in patients with type 2 diabetes mellitus (T2DM) without a history of cardiovascular or renal complications (i.e., in the early stages of T2DM) compared with patients without T2DM. Methods: We performed a retrospective cohort study using a Japanese hospital claims database. The incidence rates of comorbidities (chronic kidney disease [CKD], heart failure [HF], myocardial infarction [MI], peripheral arterial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These validation results indicate the usefulness of our model as a support tool for a wide range of clinicians in the management of patients with T2DM. Patients with T2DM are at high risk for CKD and HF, and these complications have a significant impact on their prognosis 14,45 . However, there are not enough preventive measures nor early interventions implemented for CKD and HF in patients with T2DM, and one possible cause could be a difficulty in identifying patients at a high risk of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…These validation results indicate the usefulness of our model as a support tool for a wide range of clinicians in the management of patients with T2DM. Patients with T2DM are at high risk for CKD and HF, and these complications have a significant impact on their prognosis 14,45 . However, there are not enough preventive measures nor early interventions implemented for CKD and HF in patients with T2DM, and one possible cause could be a difficulty in identifying patients at a high risk of these complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although multifactorial interventions successfully reduce the risk of atherosclerotic cardiovascular diseases in patients with T2DM [ 51 , 52 ], the incidence of HF remains high even after controlling for risk factors, including blood pressure and lipids within their target ranges [ 53 ]. Furthermore, CKD and HF develop from the early stages of T2DM and place a substantial burden on the prognosis of T2DM [ 5 , 18 ], underscoring the need for early detection and early intervention. Recent real-world studies have demonstrated that the use of SGLT2i is associated with a slower decline in renal function [ 54 ] and lower incidence of cardiovascular events [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Japanese real-world data (RWD) have further provided evidence of the frequent manifestation of HF and CKD in the early stages of T2DM [ 5 , 17 , 18 ] and clinical benefits of SGLT2i in these patients [ 19 , 20 ]. Unlike the ADA and EASD guidelines, the Japanese clinical practice guidelines do not recommend specific pharmacotherapies for T2DM, and instead endorse the selection of drugs on the basis of the patient’s disease condition.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that patients with diabetes frequently develop micro- and macrovascular complications, which worsen the prognosis and quality of life (QOL) of patients. More recently, a multinational cohort study demonstrated that HF and CKD are early and frequent complications in patients with T2DM ( 10 ), and their risk of developing these complications is double that of individuals without T2DM ( 11 ). For managing diabetic complications, glucose-lowering drugs are of great importance, together with diet and exercise therapy.…”
Section: Sglt2i For the Prevention Of Diabetic Complicationsmentioning
confidence: 99%
“…Moreover, decreased renal function is associated with an increased risk of the onset of HF and CV death ( 7 – 10 ). In fact, the prognosis of patients with concomitant T2DM, HF, and CKD is extremely poor ( 11 ). Given the vicious interactions among these disorders, holistic interventions that can simultaneously target the multiple disorders in CRM syndrome are of great importance ( 12 ).…”
Section: Introductionmentioning
confidence: 99%